Meningkatkan Kolaborasi antar Generasi di Tempat Kerja untuk Produktivitas yang lebih Baik (Kantor Desa Jombang) - Rahmawati, Ima; Nugroho Edie Santoso; Harmawan Teguh Saputra (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
Generational diversity in the modern workplace creates challenges as well as opportunities in building effective collaboration. This study aims to evaluate the conditions of intergenerational collaboration in the Jombang Village Office, identify factors that influence such collaboration, and analyze the role of technology and strategies for improving intergenerational collaboration in increasing work productivity. The research method used is quantitative-descriptive with a survey approach and in-depth interviews. Respondents consisted of 50 employees representing Generations X, Y, and Z. The results of the study indicate that the conditions of intergenerational collaboration are in the good category (average score of 3.8), but there are still challenges in communication and technology adaptation. The use of collaborative technology received the highest score (4.1), indicating its important role in bridging generations. Strategies that are considered effective include cross-generational training, open communication, and mentoring programs. This study confirms that a comprehensive strategic approach is needed to create synergy between generations in the village government environment. Keywords: Intergenerational Collaboration, Cross-Generational Training, Collaborative Technology